Sort by

- Relevance
- |Time

...it is based of conservation of mass, number of atoms in

**LHS**must equal RHS follow the links below for solution.So balanced...1 Answers · Science & Mathematics · 20/01/2013

...: tan² θ cos² θ + cot² θ sin²θ = 1

**LHS**= (sin²θ/cos²θ) × cos² θ+ (cos²θ/sinθ²...1 Answers · Science & Mathematics · 01/10/2013

...1/tanA = cotA sin(2A) = 2 * sinA * cosA

**LHS**tanA + cotA RHS 2/(2 sinA * cosA) =...1 Answers · Science & Mathematics · 29/07/2009

... sign, try to make the right hand side (RHS) equal the left hand side (

**LHS**). To start, just pick one variable for one side, and put the others on the...2 Answers · Science & Mathematics · 11/09/2012

...the transistor emitter current is I*Rs/100 (100 ohm resistor at top

**LHS**of diagram.) For large current gains in the transistor, the collector current...1 Answers · Science & Mathematics · 16/06/2015

r(t) = e^-t costi + e^-t sintj + e^-tk This shows that point (x, y, z) is parametrically (e^-t cost, e^-t sint, e^-t)

**LHS**= z^2= e^2t RHS= x^2 + y^2= e^2t( cos^2t + sin^2t )= e^2t So vector lies on cone1 Answers · Science & Mathematics · 25/09/2014

... to perform it the other way round, i.e. starting from the

**LHS**. A final point is notice that A^2+B^2=R^2((sin^2...1 Answers · Science & Mathematics · 25/04/2013

...sec(3x)*tan(3x) Since M_y is not equal to N_x, the

**LHS**of the equation is not an exact differential, and some other method of solution woulld...1 Answers · Science & Mathematics · 13/02/2014

...x(t-to)) which is equal to y(t-to)(replace t by to in the RHS and

**LHS**of the equation y(t-to) = = sin(x(t-to))). It is obvious from the relation...1 Answers · Science & Mathematics · 28/01/2014

...this to be true for k = 1 and k = k + 1 Consider k = 1 ------------------------

**LHS**= 3 RHS = 3 Thus true Consider k = k + 1...1 Answers · Science & Mathematics · 18/05/2012